SANEAMENTO AMBIENTAL NO MARANHÃO: uma análise do financiamento e do gasto público no período de 2009 a 2018 - Jose Rui Moreira Reis (Universidade Federal do Maranhão, 2020)
Considering sanitation policy as a central aspect of contemporary environmental issues, the article addresses to concepts and principles present in Federal Law 11.445/07 and analyzes the financing and public spending on basic sanitation policies implemented by the State of Maranhão from 2009 to 2018, highlighting the amount, relevance, management, destination and funding sources of these policies. At the methodological level it is based on the critical analysis of financing and budget spending. The results show a reduction in the relevance of sanitation spending in the last decade, the Maranhão Environmental Sanitation Company as the main public institution operating in the area, the administration expenses as the main destination of resources, the prioritization of water supply expenses, and tariffs as the main source of resources.